2005
DOI: 10.1039/b504635a
|View full text |Cite
|
Sign up to set email alerts
|

Structuring of bridged silsesquioxanes via cooperative weak interactions: H-bonding of urea groups and hydrophobic interactions of long alkylene chains

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 36 publications
1
57
0
Order By: Relevance
“…[33][34][35] Small ¢ values (on the order of 40-60 cm -1 ) are related to strong H-bonds, while ¢ values in the range 70-100 cm -1 are characteristic of less strong H-bonds. 18,20,21 Using the maximum of the fitted Lorentzian peaks, the resulting values for our samples are ¢ -(U-1) ) 106 cm -1 and ¢ (U-2) ) 102 cm -1 . These values are located in the range where hydrogen bonds cannot be characterized as strong, with the more ordered sample (U-2) exhibiting a slightly higher value of the strength of these bonds.…”
Section: Resultsmentioning
confidence: 99%
“…[33][34][35] Small ¢ values (on the order of 40-60 cm -1 ) are related to strong H-bonds, while ¢ values in the range 70-100 cm -1 are characteristic of less strong H-bonds. 18,20,21 Using the maximum of the fitted Lorentzian peaks, the resulting values for our samples are ¢ -(U-1) ) 106 cm -1 and ¢ (U-2) ) 102 cm -1 . These values are located in the range where hydrogen bonds cannot be characterized as strong, with the more ordered sample (U-2) exhibiting a slightly higher value of the strength of these bonds.…”
Section: Resultsmentioning
confidence: 99%
“…The self-organization of these hybrid materials is imposed by the rigidity of the organic groups chemically bonded in a bridged way to the inorganic moiety. [11][12][13][14][15] In recent times it was demonstrated that self-organized materials can also be obtained using bridging charged organic groups. 16,17 It is important to point out that the selforganization in silica-based hybrid material has always been associated with the presence of bridging organic groups.…”
Section: Introductionmentioning
confidence: 99%
“…Self-assembly can occur previous to or during the polycondensation of terminal groups, induced by strong hydrogen bonds, aromatic p-stacking, or van der Waals interactions between (CH 2 ) n groups. [15][16][17][18][19][20][21][22][23][24][25][26] When the self-assembly and polycondensation processes take place simultaneously, the organization attained in the final material depends on their relative rates. [26] A variety of structures and properties has been reported for self-assembled bridged silsesquioxanes.…”
Section: Full Papermentioning
confidence: 99%
“…[21] Long-range ordered lamellar structures with a macroscopic organization in compact sheets were obtained combining the association properties of urea groups by H-bonds and those of long hydrocarbon chains. [17,18,[22][23][24] The selfassembly could also be produced just by the hydrophobic interactions between long alkylene chains. [25] The aim of this study was to generate a new family of bridged silsesquioxanes using a precursor synthesized by the reaction of a primary amine (1 mol) with glycidoxypropyl(trimethoxysilane) (GPMS, 2 mol) ( Figure 1).…”
Section: Full Papermentioning
confidence: 99%